Breakeven Installed Costs of Off-Grid Solar PV System for Groundwater Irrigation - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This data set contains GIS source data files showing breakeven installed costs for solar PV system (unit: US$/Wp) over Africa South of Sahara calculated in a study that compares the economic cost of groundwater pumping for irrigation powered by solar PV and diesel energy. It consists of three sets of data files for three scenarios: Breakeven installed cost calculated under reference diesel fuel price scenario (price escalation rate=2%); Breakeven installed cost calculated under high diesel fuel price scenario (price escalation rate=4%); Breakeven installed cost calculated under low diesel fuel price scenario (price escalation rate=0).